Corporate entrepreneurial orientations in state owned enterprises in Malaysia - Harry, Entebang (Universiti Malaysia Sarawak, (UNIMAS), 2006)
The growth of Government Linked Companies (GLCs) in Malaysia has been phenomenal in terms of investment, production, revenue and range of activities. GLCs constitute a substantial portion ofthe Malaysian economy and they have been regarded as instruments of national growth, supplementing the Government's efforts to promote the social and economic goals and objectives of the country. However, the performance of GLCs continues to be a major concern but research on these companies is still limited. This study will present what constitute GLCs in Malaysia, the motives behind the creation of GLCs and GLCs' basic structure in the context of corporate entrepreneurship. The study reveals that GLCs regard risk taking, proactiveness, innovativeness and competitive aggressiveness as significant variables and have influenced their corporate entrepreneurial orientation.